Community Preparation: Thai Geographical Indication Logo for Pla-Salid Bang-Bo, Samut Prakan Province - Tantawanich, Siriwan; Akarachantachote, Noppamas; Praykaew, Alissara; Chiewpricha, Yuwathida; Pumtian, Jamroonsri; Changtam, Chatchawan; Onthai, Mathuros (Area Based Development Research Journal, 2020)
The study aims to prepare farmers and processors of four districts of Samut Prakan province –Bang Bo district, Bang Phli district, Muang district, and Bang Sao Thong district – in development of Bang Bo snakeskin gourami production process to earn geographical certification and brand logo. By employing participatory action research process, researchers, farmers and processors of snakeskin gourami, as well as government agencies are involved in the study. The research process contains four phases: 1) raising awareness and knowledge on geographical certification of Bang Bo snakeskin gourami, 2) developing farming methods for Bang Bo snakeskin gourami, 3) developing dried salted snakeskin gourami processing, 4) developing a quality control system for Bang Bo snakeskin gourami production, and 5) sharing with the community, preparation plans on management. The findings indicate that the number of snakeskin gourami farmers whose production process has met geographical certification standard rises to 59.02% while the snakeskin gourami processors who meet the geographical certification standard counts for 12.5%. Moreover, a manual for quality control and quality assurance was developed for Bang Bo snakeskin gourami, which can be immediately used by Samut Prakan province. Finally, the newly developed information system promotes public relations of Bang Bo snakeskin gourami as it consists of Bang Bo snakeskin gourami database, qualification verification process, geographical certification and brand logo application process; which includes a database on communal participation and learning outcome via social media and websites.